IMPLEMENTATION OF ISLAMIC SHARIA LAWS IN EAST ACEH: The Acehnese Perspectives - Abdul Manan; Cut Intan Salasiyah (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract: This research studied the recent implementation of sharia in the district of East Aceh by employing a qualitative approach with ethnographic methods. This research focused on sociological interpretations of the data gathered through the processes of observation of social interactions that reflected demographic patterns of daily intercourse, events, and traditions. The results showed that the implementation of sharia laws triggered pros and cons within society in East Aceh. Some people argued that the government did not put maximum effort into the implementation. Many other people, however, experienced positive changes in their life due to the implementation of sharia. There are still many challenges such as weakness of faith and social activities that are now forbidden there plus different understandings of sharia law still exist. Co-operation between the governments, scholars, and the people, in particular opinion leaders will be the key to continue successful implementation.Keywords: East Aceh, The Holy Qur’an and al-Hadîts, People’s Perspectives, Islamic laws Abstrak: Penelitian ini mengkaji implementasi pelaksanaan syariat Islam di Kabupaten Aceh Timur menggunakan pendekatan kualitatif dengan metode etnografi. Penelitian ini berfokus pada interpretasi sosiologis dari data yang dikumpulkan melalui proses pengamatan interaksi sosial yang mencerminkan pola demografis hubungan sehari-hari, peristiwa, dan tradisi. Hasil penelitian menunjukkan bahwa penerapan hukum syariah memicu pro dan kontra di kalangan masyarakat di Aceh Timur. Sebagian kalangan menilai pemerintah kurang maksimal dalam pelaksanaannya. Namun, banyak orang lain mengalami perubahan positif dalam hidup mereka karena penerapan syariah. Masih banyak tantangan seperti lemahnya iman dan aktivitas sosial yang sekarang dilarang di sana ditambah pemahaman yang berbeda tentang hukum syariah masih ada. Kerja sama antara pemerintah, cendekiawan, dan masyarakat, khususnya para pemangku kebijakan akan menjadi kunci untuk melanjutkan keberhasilan implementasi hukum syariah. Kata Kunci: Aceh Timur, Al-Qur’an dan Hadist, Pandangan Masyarakat, Syariat Islam